WOOD QUALITY OF THE SPECIES Cedrelinga cateniformis Ducke THROUGH ULTRASONIC INSPECTION - Yoza, Luis Shuseki; de Matos, Jorge Luis Monteiro; da Rocha, Márcio Pereira; Blanco, Jose Carlos Sánchez; Venson, Ivan (Floresta, 2020)
The present work proposes a method of inspecting structural elements of wood blocks using non-destructive techniques. For this, three blocks of Cedrelinga cateniformis Ducke wood were longitudinally perforated in a grid form, then transversal ultrasound velocities were measured and used to make 2D graphics. Afterwards, the blocks were cut to make transversal specimens that were used to determine apparent densities. The graphs of both parameters were compared to visualize quality zones in the blocks from velocity and density bands. From this, a preliminary inspection protocol using ultrasound tests of structural elements was proposed.